COVID-19 and acute respiratory failure treated with CPAP. Issue 1 (1st January 2021) - Kofod, Linette Marie; Nielsen Jeschke, Klaus; Kristensen, Morten Tange; Krogh-Madsen, Rikke; Monefeldt Albek, Carsten; Hansen, Ejvind Frausing
ABSTRACT: Introduction: Patients admitted with COVID-19 often have severe hypoxemic respiratory insufficiency and it can be difficult to maintain adequate oxygenation with oxygen supplementation alone. There is a physiological rationale for the use of Continuous Positive Airway Pressure (CPAP), and CPAP could keep some patients off mechanical ventilation. We aimed to examine the physiological response to CPAP and the outcome of this treatment. Methods : Data from all patients admitted with COVID-19 and treated with CPAP, from March to July 2020 were collected retrospectively. CPAP was initiated on a medical ward when oxygen supplementation exceeded 10 liters/min to maintain oxygen saturation (SpO2 ) ≥92%. CPAP was administered with full face masks on a continuous basis until stable improvement in oxygenation or until intubation or death. Results: CPAP was initiated in 53 patients (35 men, 18 women) with a median (IQR) age of 68 (57–78) years. Nine patients were not able to tolerate the CPAP treatment. Median duration for the 44 patients receiving CPAP was 3 (2–6) days. The PaO2 /FiO2 ratio was severely reduced to an average of 101 mmHg at initiation of treatment. A positive response of CPAP was seen on respiratory rate (p = 0.002) and on oxygenation (p < 0.001). Of the 44 patients receiving CPAP, 12 (27%) avoided intubation, 13 (29%) were intubated, and 19 (43%) died. Of the patients with a ceiling of treatment in the ward (26 of 53) only 2 survived. Older age and high initial oxygen demand predicted treatment failure. Discussion: CPAP seems to have positive effect on oxygenation and respiratory rate in most patients with severe respiratory failure caused by COVID-19. Treatment with CPAP to severely hypoxemic patients in a medical ward is possible, but the prognosis for especially elderly patients with high oxygen requirement and with a ceiling of treatment in the ward is poor.